2011
DOI: 10.1016/j.molcel.2011.03.026
|View full text |Cite
|
Sign up to set email alerts
|

The Specificity and Topology of Chromatin Interaction Pathways in Yeast

Abstract: Summary Packaging of DNA into chromatin has a profound impact on gene expression. To understand how changes in chromatin influence transcription, we analyzed 165 mutants of chromatin machinery components in Saccharomyces cerevisiae. mRNA expression patterns change in 80% of mutants, always with specific effects, even for loss of widespread histone marks. The data is assembled into a network of chromatin interaction pathways. The network is function-based, has a branched, interconnected topology and lacks stric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
258
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(289 citation statements)
references
References 65 publications
30
258
1
Order By: Relevance
“…S3 B and C and Dataset S1). Consistent with previous work (27), swi2-Δ10R did not affect SIR2 or SIR3 expression (Fig. S3D and Dataset S1).…”
supporting
confidence: 92%
“…S3 B and C and Dataset S1). Consistent with previous work (27), swi2-Δ10R did not affect SIR2 or SIR3 expression (Fig. S3D and Dataset S1).…”
supporting
confidence: 92%
“…SET1 Deletion Causes Increased CTD Serine 5 Phosphorylation-Although cells lacking SET1 exhibit changes in the transcription levels of some genes (12,37), they often show alterations in the induction or repression kinetics of regulated genes (13,38,39). Deletion of SET1 also confers sensitivity to the drug 6AU (20), which slows transcription elongation by depleting NTP pools.…”
Section: Resultsmentioning
confidence: 99%
“…S5A) nor does it cause a significant change in the expression levels of other splicing proteins. 71 Utilizing antibodies that recognize either the HA-tag found in the splicing proteins or the Rpb3 subunit of RNA Pol II, we found that deletion of SET2 resulted in a significant decrease in association of Lea1-HA in both the intron regions of the RPS21B and SRB2 genes (p < 0.05) as well as the some of the exon regions of the premRNA (Fig. 6B).…”
Section: Association Ofmentioning
confidence: 92%